2000
DOI: 10.1046/j.1365-2443.2000.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Rev‐dependent association of the intron‐containing HIV‐1 gag mRNA with the nuclear actin bundles and the inhibition of its nucleocytoplasmic transport by latrunculin‐B

Abstract: Background: A hallmark of HIV-1 gene expression is that unspliced genomic RNA, which also acts as mRNA for the expression of Gag/Pol, is exported to the cytoplasm. Rev directs this transport through the nuclear export signal (NES).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
52
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 65 publications
5
52
1
Order By: Relevance
“…The first site, AB-1, is shared and conserved in all lamins whereas the second site, AB-2, is unique to lamin A. F-actin bundles were detected by rhodamine-phalloidin labeling and by TEM imaging, suggesting lamin-mediated bundling was not an artifact of centrifugation in the high-and low-speed pelleting assays. These findings suggest potential concerted mechanisms for pathways that are known to require both polymerizable actin and A-type lamins, such as mRNA export, [36][37][38][39] intranuclear chromatin movement 40,41 and transcription. 5,[42][43][44] Although nuclei lack phalloidin-stainable F-actin, approximately 20% of actin in the nucleus is found in alternative polymeric state(s).…”
Section: Discussionmentioning
confidence: 93%
“…The first site, AB-1, is shared and conserved in all lamins whereas the second site, AB-2, is unique to lamin A. F-actin bundles were detected by rhodamine-phalloidin labeling and by TEM imaging, suggesting lamin-mediated bundling was not an artifact of centrifugation in the high-and low-speed pelleting assays. These findings suggest potential concerted mechanisms for pathways that are known to require both polymerizable actin and A-type lamins, such as mRNA export, [36][37][38][39] intranuclear chromatin movement 40,41 and transcription. 5,[42][43][44] Although nuclei lack phalloidin-stainable F-actin, approximately 20% of actin in the nucleus is found in alternative polymeric state(s).…”
Section: Discussionmentioning
confidence: 93%
“…D, the densitometric scan is shown. Protein loading for both cytoplasmic and nuclear Western blots was normalized to ␤-actin as described (33). E, HC11 cells were transfected with 1.0 g of the cDNA expression clone for p38␣ and the indicated concentrations of the pMKK6bE expression clone, and EMSA analysis was performed on nuclear and cytoplasmic fractions using the mouse XOR Ϫ140/Ϫ170 C/EBP␤ oligonucleotide.…”
Section: Discussionmentioning
confidence: 99%
“…Oncogene (2003Oncogene ( ) 22, 627-631. doi:10.1038 Actin plays central roles in cell motility processes such as cytokinesis, cell locomotion, exocytosis and endocytosis through formation of the actin cytoskeleton (Mitchson and Cramer, 1996). Recently, the possibility that actin also functions in the cell nucleus, probably mainly in monomer form (Zhao et al, 1998;Kimura et al, 2000;Rando et al, 2000;Wasser and Chia, 2000), has been emerging. For example, b-actin monomer has been suggested to be a functional component of the mammalian SWI/SNF-like BAF complex (Zhao et al, 1998).…”
mentioning
confidence: 99%
“…For example, b-actin monomer has been suggested to be a functional component of the mammalian SWI/SNF-like BAF complex (Zhao et al, 1998). It has also been suggested that nuclear b-actin bundles may be involved in the HIV Rev-dependent regulation of nucleocytoplasmic transport of viral mRNA (Kimura et al, 2000). To dissect its dynamics and functions, several actin-disrupting drugs have been widely and effectively employed.…”
mentioning
confidence: 99%
See 1 more Smart Citation